Effect of Moringa oleifera seeds on the removal of pathogens and pharmaceutical residues in a domestic wastewater treatment plant by an interdisciplinary approach - Sané, Nini; Sivalingam, Periyasamy; Koželuh, Milan; Mbengue, Malick; Stoll, Serge; Poté, John; Le Coustumer, Philippe (Environmental science and pollution research international, 2024)
In this transdisciplinary study, we investigated, using genomic tools and physico-chemical parameters, the effect of Moringa oleifera seed (MOS) on the removal of microorganisms and pharmaceutic residues (antibiotics), and also the development of antibiotic-resistant genes (ARGs) in water samples from a domestic wastewater treatment plant (WWTP) prototype. Water samples were analyzed with and without the addition of powder of MOS. The results showed that MOS addition reduced the total bacterial load from 1.73 × 1010 ± 3.21 × 109 to 6.67 × 106 ± 5.77 × 106 CFU/L, while fecal coliforms and Escherichia coli were removed with efficiencies of 99% and 57%, respectively. Furthermore, MOS treatment resulted in a reduction in fecal coliforms and E. coli resistant to ampicillin by about 100% and 96%, respectively. The results indicated that ciprofloxacin removal efficiencies at 29 °C were over 93% (fecal coliforms) and 68% (E. coli) with doxycycline. Adding MOS significantly reduced the copy number of the 16S rRNA gene and the genes conferring resistance to β-lactam (blaCTX-M, blaSHV, and blaTEM). However, MOS does not reveal real effectiveness on removal of pollutants (phosphorus and nitrates) contrary to what was expected. Additional studies are needed for confirmation from our observations. The findings of this study, whatever the functioning conditions (not optimal) of the prototype followed over 4 years, confirmed that MOS is potentially an effective natural and environmentally friendly coagulant that could be applied to wastewater treatment in low-income countries to remove or minimize multiple pollutants and control ARG spread. To promote sustainable development, this small-scale study provides guidance for designing infrastructure in resource-limited locations to take advantage of MOS effects in wastewater treatments.
Keywords: odpad tekutý - odstraňování; Escherichia coli; Pollutants; Wastewater; Seeds; semena rostlinná; Moringa oleifera seeds; Moringa oleifera; čištění vody; Antibiotic resistant; Anti-Bacterial Agents; Waste Disposal, Fluid; Natural coagulant; odpadní voda; Water Purification; Genomic; Resistant genes; Prototype; antibakteriální látky; Pharmaceutic residues